Ancaman Perubahan Iklim di Pulau Kecil: Studi Kasus Kerentanan Ekologis Pulau Bawean - Styawan, Wahyu Eka (ECOTAS, 2024)
Climate change has a significant impact on small islands, including Bawean Island, which faces various threats such as rising sea levels, increasing temperatures, and the degradation of marine ecosystems, particularly coral reefs. This study aims to assess the ecological vulnerability of Bawean Island to climate change and the adaptive strategies employed by the local community, especially fishermen. The results show that climate change affects the livelihood of fishermen through changes in weather patterns, seasonal cycles, and reduced fish catches. Bawean's fishing communities have developed various adaptive strategies, such as avoiding the use of destructive fishing gear, utilizing local knowledge of winds and seasons, and participating in conservation programs like mangrove planting to mitigate coastal erosion. This study emphasizes the importance of a human ecology approach in understanding community adaptation to climate change. These adaptations not only involve responses to physical environmental changes but also social and economic engagement influences community resilience. The study recommends the need for policy interventions that support ecosystem sustainability and the development of environmentally friendly technologies to enhance the adaptive capacity of Bawean Island's communities in the face of future climate change impacts.